Flipping the Logic Classroom in advance Arguments For and Challenges Addressed. - Pearlman, S.
Despite increasing evidence that the traditional lecture is inefficient for student learning, such methods remain the central paradigm for teaching logic. In this paper, I identify the deficits of the lecture model and outline the many benefits of flipping the logic classroom?namely that students can absorb information at their own pace, freeing classroom time for active learning activities, and allowing the students to come prepared to actively engage in deeper levels of learning. I provide advice for curricular change from the traditional model, and guidance for flipped classroom implementation. I also offer suggestions for the best use of newly available class time, and advice for keeping students accountable for learning the information prior to class. Last, I consider common challenges with the flipped classroom model. I acknowledge possible obstacles to flipping the undergraduate logic course and address these challenges with potential solutions.